Comparison of the effectiveness of rocking and massage on infant sleep quality using a local wisdom approach in Barito Kuala Regency, South Kalimantan Province - Eka Damayanti; Mufdlillah Mufdlillah; Asri Hidayat (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Infant sleep quality is an important determinant of growth, neurodevelopment, immune function, and family well-being. In South Kalimantan, traditional rocking practices such as bapukung remain culturally familiar, yet their effectiveness compared with infant massage has not been adequately examined. Objectives: This study aimed to compare the effectiveness of rocking and infant massage in improving sleep quality among infants aged 0-12 months in the working area of Tamban Community Health Center, Barito Kuala Regency, South Kalimantan, Indonesia. Methods: A quasi-experimental study with a non-equivalent control group design was conducted from March to June 2025. Seventy-six infants were selected through purposive sampling and allocated into two groups: rocking (n=38) and infant massage (n=38). Rocking was performed using a traditional/manual rhythmic swing three times daily for 5-25 minutes, adjusted to infant comfort, whereas infant massage was performed once daily before bedtime for 10-15 minutes using a structured gentle massage procedure. Sleep quality was measured before and after the 5-week intervention using the Brief Infant Sleep Questionnaire (BISQ). Changes in sleep quality categories were analyzed using the McNemar test with a significance level of p<0.05. Results: The proportion of infants with good sleep quality in the rocking group increased from 39.5% before intervention to 60.5% after intervention, and the change was statistically significant (p=0.008). In the massage group, good sleep quality increased from 44.7% to 60.5%, but the change was not statistically significant (p=0.180). Conclusions: Rocking was more effective than infant massage in improving infant sleep quality. Culturally relevant education on safe rocking techniques may be integrated into community-based infant health promotion programs.